Strategi mitigasi risiko perbankan syariah indonesia dalam merespons ketidakpastian geopolitik dan disrupsi digital: Studi literatur konflik Rusia-Ukraina - Pramudita, Defrangga Piyu (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze risk mitigation strategies applicable to Indonesian Islamic banking in responding to global geopolitical uncertainty and digital disruption, particularly those triggered by the Russia-Ukraine conflict. The research adopts a literature review method by examining various scholarly articles, empirical studies, and recent publications related to risk management, geopolitics, and digital transformation in the Islamic banking sector. The findings indicate that the risks faced by Islamic banks are multidimensional, encompassing financial, reputational, technological, and internal governance aspects. The study reveals that effective mitigation strategies include policy flexibility, the strengthening of Sharia-based governance, the utilization of digitalization as a mitigation tool, and the enhancement of internal oversight through a more active role of the Sharia Supervisory Board. By integrating lessons from the pandemic, core Sharia principles, and global adaptive responses, this study recommends the development of a more holistic, adaptive, and sustainable risk mitigation framework for the future of Islamic banking in Indonesia.